INFLUENCE OF MURABAHAH RECEIVABLES, MUSYARAKAH FINANCING, AND LEASE FINANCING ON PROFITABILITY OF BANK ACEH SYARIAH - Novia Nengsih; Rizal Rizal; Yeni Melia (Imara: JURNAL RISET EKONOMI ISLAM, 2023)
Background. The profitability in Islamic bank is influenced by murabahah receivables, musyarakah financing and lease financing. Therefore, it is essencial to analysis profitability in PT. Bank Aceh. Effectiveness of oral corrective feedback (OCF) in language learning is influenced by learners’ comprehension and response to various OCF techniques. Therefore, it is essential for teachers to consider learners’ preferences for OCF strategies.Purpose. This research aims to analyze the influence of Murabahah, Musyarakah, and Lease Receivables on the profitability of Bank Aceh Syariah.The population of this study is Islamic Banks in Indonesia in 2012-2017 are 13 BUS.Method. The data was analyzed using multiple linear regression analysis, path analysis, and sobel test. This research is a field study with a quantitative approach. The data used in this study is secondary data in the form of Financial Statements quarter 2017 to November 2020 registered with the Financial Services Authority (OJK). This type of research data is panel data that are analyzed using descriptive statistics, classical assumptions, and multiple linear regressions.Results. The results showed that there was no effect of murabahah receivables on the profitability of PT. Bank Aceh with a significance of 0.938, with alpha (α) 0.05 or 5%.  The effect of musyarakah financing on profitability in PT. Bank Aceh with the significance of 0.010 with alpha (α) 0.05 or 5%. The absence of the effect of lease / ijarah on profitability in PT. Bank Aceh with the significance of 0.082, with alpha (α) 0.05 or 5%. There is a significant influence between murabahah receivables, musyarakah financing, and simultaneous lease financing on the profitability of PT. Bank Aceh period 2017-2020 is 26% while the remaining 74% is determined or influenced by other variables that are not included in this study.Conclusion. This study has significant implications for assessing profitability in Islamic bank bg using murabahah receivables, musyarakah financing and lease financing.